This Beach is Loud! - Cotterill, Samantha (New York, NY : Dial Books for Young Readers, 2019)
"A sensitive boy gets overwhelmed by all the sights, sounds, and sensations at the beach, but his dad has a trick to help his son face these unexpected obstacles"--
Keywords: Senses and sensation -- Juvenile fiction; Beaches -- Juvenile fiction; Anxiety in children -- Juvenile fiction; Senses and sensation -- Fiction; Beaches -- Fiction; Anxiety in children -- Fiction; JUVENILE FICTION / Social Issues / Special Needs; JUVENILE FICTION / Social Issues / Emotions & Feelings; JUVENILE FICTION / Social Issues / New Experience